Toxicological assessment and inseсtoacaricid efficiency of the preparations «RolfСlub 3D Spray for Dogs» and «RolfСlub 3D Spray for Cats» - V. A. Stepanov; M. V. Arisov; E. S. Smirnova (Российский паразитологический журнал)
The toxicological assessment is given and efficiency of complex preparations is studied. «RolfClub 3D spray for dogs» contains fipronil, D-cifenotrin, piriproxi-fen; «RolfСlub 3D spray for cats» – fipronil, etofenprox, piriproxifen. Preparations represent solution and are applied spot on as spray. Parameters of acute and skin toxicity of preparations for dogs and for cats are determined. LD50 at introduction in a stomach to mice made 5809±508,6 and 4295±607 mg/kg respectively, LD50 when drawing on skin to rats – more than 30000 mg/kg (the 4th class of danger). Preparations don't possess local irritating action. At application in twice and five time increased doses during 7 days have no negative impact on the general condi-tion of dogs and cats, their physiological status and behavior, don't change morpho-logical structure and biochemical indicators of blood and urine. Preparations pos-sess accurately expressed insektoakaricid activity on all stages of development of fleas, louses, ticks of the genius Sarcoptes and Demodex. Preparations don't cause side effects and complications.